Inhibition of hedgehog signalling attenuates UVB‐induced skin photoageing. Issue 8 (26th May 2015) - Kim, Wanyeon; Kim, EunGi; Yang, Hee Jung; Kwon, TaeWoo; Han, SeoYoung; Lee, Sungmin; Youn, HyeSook; Jung, Youngmi; Kang, ChulHee; Youn, BuHyun
Abstract The hedgehog (Hh) signalling pathway regulates normal development and cell proliferation in metazoan organisms, but its aberrant activation can promote tumorigenesis and progression of a variety of aggressive human cancers including skin cancer. Despite its importance, little is known about its role in photoageing, a type of UV‐induced skin lesions. In this study, we investigated the involvement of Hh signalling in the photoageing process as well as the use of an Hh‐regulating alkaloid compound as a novel therapeutic drug to regulate photoageing in keratinocytes. We found that UVB induced Hh signalling by the expression of Hh ligands and Hh‐mediated transcription factors, respectively. Moreover, UVB‐induced Hh activation relied on mitogen‐activated protein kinase (p38, ERK and JNK) activity and inflammatory responses (upregulation of COX‐2, IL‐1β, IL‐6 and TNF‐α), resulting in premature senescence and photoageing in vitro and in vivo. Notably, a selected Hh inhibitor, evodiamine, mediated photoageing blockade in a mouse skin model. Taken together, our findings demonstrated that Hh signalling is associated with UVB‐induced photoageing, while pharmacological inhibition of Hh signalling significantly reduced experimental photoageing, indicating its potential for use as a therapeutic target for this disease.